Safety and efficacy of methyl cellulose for all animal species. (31st July 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on methyl cellulose as a feed additive for all animal species. Methyl cellulose is intended for use as a technological additive (functional groups: emulsifier, stabiliser, thickener, gelling agent and binder) in premixtures and feedingstuffs for all animal species with no minimum and maximum content. A proper identification and characterisation of methyl cellulose as required for a feed additive is not available and the occurrence of potential toxic impurities cannot be assessed. The following conclusions apply only to methyl cellulose meeting the food additive specifications. The FEEDAP Panel concluded that methyl cellulose is considered safe for all animal species. The use of methyl cellulose in animal nutrition is of no concern for consumer safety. In the absence of data, the FEEDAP Panel was not in the position to conclude on the safety of methyl cellulose for the user. The use of methyl cellulose as a feed additive is considered safe for the environment. The additive is considered to be efficacious in feedingstuffs for all animal species.